2007
DOI: 10.1111/j.1600-0501.2007.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Speech adaptation after treatment of full edentulism through immediate‐loaded implant protocols

Abstract: Immediate loading of oral implants does not seem to compromise the normal 3-6 months speech adaptation period. Whether such procedure presents advantages to the conventional 2-stage rehabilitation remains to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 10 publications
4
24
0
3
Order By: Relevance
“…The among-groups comparison showed no significant difference. This can be attributed to sample size as individual analysis revealed lower PCC values in groups B and C for alveolar and dental phonemes which agrees with studies showing that these are the mostly altered phonemes after insertion of total dentures (2,11,15,16).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The among-groups comparison showed no significant difference. This can be attributed to sample size as individual analysis revealed lower PCC values in groups B and C for alveolar and dental phonemes which agrees with studies showing that these are the mostly altered phonemes after insertion of total dentures (2,11,15,16).…”
Section: Discussionsupporting
confidence: 76%
“…A study reported that the use of conventional prostheses for a long period can harm the adjustment of new prostheses and may require professional help (11). In the current study, three patients have used prostheses for over 10 years and, on the individual analysis, two of them presented no speech alteration.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this type of comparison would have no clinical significance, because all types of dental prostheses requires an adaptation period. Recently, it was verified that the adaptation period for speaking among patients that received immediate protocol-type prostheses was 3 to 6 months [15]. Considering the lower extension of the ISP in the present study, it is possible to realize that the adaptation period for our sample group patients was one month.…”
Section: Discussionmentioning
confidence: 80%
“…They do not evaluate continuous speech but often only single vowels or consonants [1][2][3]. However, this does not reflect real-life communication because no speech but only the voice is examined.…”
Section: Introductionmentioning
confidence: 99%